REDD+ in Theory and Practice: How Lessons From Local Projects Can Inform Jurisdictional Approaches - Wunder, Sven; Duchelle, Amy E.; Sassi, Claudio de; Sills, Erin O.; Simonet, Gabriela; Sunderlin, William D. (Frontiers in Forests and Global Change, 2020)
Subnational projects for reducing emissions from deforestation and forest degradation (REDD+) were frequently designed as pilot actions to inform future upscaled initiatives. Drawing lessons from these project experiences may thus help improve the design of jurisdictional-level actions. Here we scrutinize how REDD+ was historically conceptualized, the most prominent model being that of a multitier payments for environmental services (PES) scheme of ‘passing on’ carbon mitigation responsibilities and credits across scales, from international buyers to forestland owners. Using a database of 226 conservation-oriented REDD+ projects, in a principal component analysis we identify three main clusters: public, private-commercial, and NGO type of initiatives. Only 88 projects had planned conditional payments to landowners—the key feature of PES. Intentions to apply PES rise after 2007, and correlate strongly with efforts in seeking certification, including as a benefit-sharing strategy, and with carbon sales. Zooming closer into a portfolio of 23 implemented local REDD+ initiatives, we found project proponents reported conditional incentives as potentially being both the most promising and effective intervention. Likewise, treated households identify conditional incentives as comparatively effective in changing their land-use plans, while also providing above-average welfare returns. Still, these conditional incentives remained underutilized in implementation, with only one-third of the treatment intensity compared to non-conditional incentives. Only 39% of project proponents believed that conditional incentives would eventually become their single-most important tool, citing insecure land tenure impeding effective contracting of land stewards, and the REDD+ insecurity in financial flows jeopardizing longer-term contractual arrangements as key limitations. The original vision of a multitier PES model for REDD+ thus ran into both supply and demand side problems, jointly explaining the discrepancy between REDD+ theory and practice. Since jurisdictional climate approaches so far also receive only hesitant and slow climate financing flows, coming mostly in non-conditional form, and operate under forest-frontier governance with similar tenure restrictions, jurisdictions would seem well-advised to only rely significantly on conditional landowner incentives in scenarios where the preconditions for PES are met.